Women And Work - Abdelhakem, Slimane (جامعة الوادي - University of Eloued, 2023)
Abstract: This paper aims at the working women issue. Starting with an introduction. Then it states The World Economic Forum report adopting policies to encourage the incorporation of women into the world of work. Women roles in companies are mentioned .The role of women regarding work, and their role in society. Discrimination against women worldwide. The study states the women's liberation movement starting with French Revolution, then the feminist movements in England and the American women's liberation movement. The study highlights the Algerian women and work, the position of Islam and the West towards them. Their hidden tasks, unappreciated by society. The study reveals the gender differences in the use of information technology. The most important part of the paper and the core of the study gives the advantages of working women; professional satisfaction, their psychological aspect, their economic independence, and how they manage time effectively. The study goes to the other side of the issue that is the disadvantages; children’s educational neglect. The disadvantages of a woman's work vis-à-vis her household. The conclusion gives the author point of view concerning the women’s work.
مقال
Keywords: Women’s work, Advantages, Disadvantages, Discrimination, Women's liberation movement